2015
DOI: 10.1021/acs.cgd.5b00127
|View full text |Cite
|
Sign up to set email alerts
|

Linear Deracemization Kinetics during Viedma Ripening: Autocatalysis Overruled by Chiral Additives

Abstract: Viedma ripening proceeds through an autocatalytic feedback mechanism which exponentially deracemizes an initially racemic solid state to an enantiopure end state. Here we show that, in the presence of enantiopure additives with a concentration of as low as 2.5 × 10 −2 mol %, Viedma ripening proceeds with an overall linear and faster increase in enantiomeric excess. These experimental results can be explained using a simple model which assumes a difference in growth and dissolution rates between the enantiomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…!,! ) > 0, growth occurs, while the case of Similarly to previous models 18,39,51,52 , due to the Gibbs-Thomson effect, the cluster solubility ! "…”
Section: Growth and Dissolutionmentioning
confidence: 76%
See 1 more Smart Citation
“…!,! ) > 0, growth occurs, while the case of Similarly to previous models 18,39,51,52 , due to the Gibbs-Thomson effect, the cluster solubility ! "…”
Section: Growth and Dissolutionmentioning
confidence: 76%
“…amino acids [4][5][6][7] and pharmaceuticals [8][9][10] that crystallize as conglomerate crystals by incorporating a fast racemization reaction. The outcome of the deracemization process depends on the initial conditions 11,12 : mass or crystal size distribution (CSD) imbalance between the enantiomers 1,[13][14][15] , presence of chiral impurities 16 or additives [17][18][19] or circularly polarized light 20 . In addition, the total time to enantiopurity varies drastically for different compounds, sometimes leading to very long processing times.…”
Section: Introductionmentioning
confidence: 99%
“…In their study though, a heating plate was used to create a strong temperature gradient, which according to the author's interpretation enhanced crystal dissolution in hot zones and crystal growth in cold zones, effectively leading to deracemization 26 . Temporal temperature variations have also been shown to induce enantiomeric enrichment in a similar manner 28,29,44 . However, such effects can be excluded in the present study, since a heating jacket was used to create a homogeneous and controlled temperature profile in the reactor, which remained essentially constant for the entire duration of the experiments.…”
Section: Resultsmentioning
confidence: 94%
“…Viedma ripening (VR) and temperature cycle‐induced deracemization (TCID) are key approaches to deracemization and are being actively studied. We recently reported that second‐order asymmetric transformation (SOAT), a combination of preferential crystallization (PC) and racemization, could achieve relatively high process productivity compared with TCID due to the short processing time.…”
Section: Introductionmentioning
confidence: 99%